2015
DOI: 10.1186/s12913-015-0815-2
|View full text |Cite
|
Sign up to set email alerts
|

Workforce interventions to improve access to emergency contraception pills: a systematic review of current evidence in low- and middle-income countries and recommendations for improving performance

Abstract: BackgroundEmergency contraceptive pills (ECP) are one of the 13 essential commodities addressed by the UN Commission on Life-Saving Commodities for Women and Children. Although ECP have been available for 20 years, a number of barriers still limit women’s access ECP in low and middle-income countries (LMIC). The workforce who prescribe or dispense ECP are diverse reflecting the varied contexts where ECP are available across the health, commercial and justice sectors and in the community. No reviews currently e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Even though the results point toward an underestimation of the number of current EC users, they also support the notion that in many geographies, EC use remains extremely low (Dawson et al. 2015; Westley et al. 2013).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Even though the results point toward an underestimation of the number of current EC users, they also support the notion that in many geographies, EC use remains extremely low (Dawson et al. 2015; Westley et al. 2013).…”
Section: Discussionsupporting
confidence: 59%
“…Even in countries where there are no government-or provider-imposed obstacles to procurement, stock outs are common (Dawson et al 2015). The issue is further exacerbated by lack of guidance on how to improve commodity security and logistics for this important contraceptive method (Dawson et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the findings of this study, previous research has found that young women generally find ECPs an acceptable and convenient option that fill the need of a post-coital contraception that can be taken as needed [4, 5, 7, 25]. However, our results also contribute to the growing evidence on barriers to ECP access and use, including myths and misconceptions about risks of ECPs [5, 25, 34, 35, 40], poor knowledge of correct usage [13, 34, 39], and restrictive distribution practices of pharmacists and health care providers [4144].…”
Section: Discussionmentioning
confidence: 60%
“…Some of the bias around it overlaps strongly with the bias around provision to youth, for example, believing that it leads to promiscuity. A 2015 review of improving access to emergency contraception through workforce interventions found widespread misconceptions among providers, including the belief that it was an abortifacient or that access to it would increase sexual activity among adolescents 25 . Using survey data in Kenya and Ethiopia to explore bias around emergency contraception, Judge et al 26 found that counseling on and provision of emergency contraception was positively associated with providers' greater level of knowledge of the method, indicating that increasing provider knowledge can potentially contribute to offsetting some of the bias and improving access.…”
Section: Resultsmentioning
confidence: 99%